2011
DOI: 10.4103/0974-620x.91271
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab in the treatment of recurrent idiopathic bilateral nodular scleritis

Abstract: Our objective is to report a case of bilateral nodular scleritis in a 34-year-old patient, resistant to steroids and traditional disease modifying anti-rheumatic drugs, who was successfully treated with subcutaneous injections of 40 mg adalimumab. Adalimumab resulted in rapid control of scleritis in both eyes within 3 months with no recurrence over 5 years of follow-up. No side effects were reported during treatment.Although a large prospective study and a longer follow-up are required to reach a conclusive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Adalimumab has been reported as successful in the treatment of bilateral idiopathic nodular scleritis (with no side effects reported) [ 8 ] and nodular scleritis associated with RA [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adalimumab has been reported as successful in the treatment of bilateral idiopathic nodular scleritis (with no side effects reported) [ 8 ] and nodular scleritis associated with RA [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first case reports and small case series of non-infectious scleritis successfully treated with adalimumab (ADA) [12][13][14][15][16] were followed by retrospective studies assessing its efficacy in larger samples of refractory patients [7,11,[17][18][19]. Ragam et al conducted a retrospective chart review of 17 patients with noninfectious, non-necrotizing scleritis and found that monoclonal anti-tumor necrosis factor alpha (TNFa) were able to reduce scleral inflammation and to concomitantly reduce the use of systemic GCs.…”
Section: Adalimumabmentioning
confidence: 99%
“…101 There are a few case reports of its use in refractory scleritis with good effect. 102, 103 Given the class effect, it is likely that adalimumab would be effective in larger series as well, though further data are needed to verify a treatment effect. A rare hepatosplenic lymphoma has been reported mostly in children receiving both adalimumab or other TNF inhibitor and azathioprine 104 .…”
Section: Current Opinionsmentioning
confidence: 99%